Jongueiros do Tamandaré : o jongo é da nação, e os jongueiros aonde vão? - Netto, Andréia da Silva (2010)
This dissertation ponders over the reconfiguration possibilities of National Identity opened during the legitimation process and the national officialization of jongo into a Jongo´s community situated in Tamandaré, at a Paraiba´s valley city of Guaratinguetá. Successes and difficulties are argued while this process occurs more specifically to the fifteen last years in that locality, contextualizing the process in this moment of national identity reconfiguration and comparing it with the context of nation configuration and of the racial democracy´s myth until the middle of the 20th century. From it on the process of legitimation and officialization of jongo in that place are critically and contemporaneously reading to shown the Afro- Brazilian as an affirmative identity and to allow the realization of construction and reconstruction of difference, which exemplifies how the national identity reconfiguration can be thought and realized together with the difference idea.